Profitability Moderates Capital Intensity And Leverage Toward Tax Aggressiveness - Raharjo, Naura Zalfa Prinda; Rustam, Akie Rusaktiva (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study examines the effects of capital intensity and leverage on tax aggressiveness, with profitability serving as a moderating variable. It utilizes secondary data obtained from the official websites of IDX and respective companies. The population comprises manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2023 period, from which a sample of 51 companies across five periods is selected using purposive sampling. To analyze the data, multiple linear regression test and moderated regression analysis (MRA) are employed. The results of this study indicate that capital intensity, as well as its interaction with profitability, may contribute to increased tax aggressiveness. In contrast, leverage is found to mitigate tax aggressiveness. However, the interaction between leverage and profitability does not appear to affect tax aggressiveness, suggesting that leverage, when moderated by profitability, does not increase tax aggressiveness.